Propriedades físicas de snacks de farinha de folhas de mandioca - Ferrari, Adriana Cristina [UNESP]; Leonel, Magali [UNESP]; Mischan, Martha Maria [UNESP] (Univ Estadual Londrina, 2014)
The food industry is continually growing with new products becoming available every year. Extrusion combines a number of unit operations in one energy efficient rapid continuous process and can be used to produce a wide variety of snacks foods. The objective of this study was to evaluate the effect of extrusion temperature, screw speed, and amount of cassava leaf flour mixed with cassava starch on the physical properties of extruded snacks processed using a single screw extruder. A central composite rotational design, including three factors with 20 treatments, was used in the experimental design. Dependent variables included the expansion index, specific volume, color, water absorption index, and water solubility index. Among the parameters examined, the amount of cassava leaf flour and extrusion temperature showed significant effects on extruded snack characteristics. Mixtures containing 10% of cassava leaf flour extruded at 100 degrees C and 255 rpm shows favorable levels of expansion, color, water absorption index, and water solubility index.
Physical properties of snacks made from cassava leaf flour
Keywords: Extrusion; protein; starch; Manihot esculenta Crantz